PRODUCTION PERFORMANCE OF CROSSING LANDRACE PIG IN THE STARTER PHASE THAT WAS FEEDED WITH ADDITIONAL YEAST CULTURE - I G. A. N. C., Wiguna; Bidura, I G .N. G.; Wibawa, A. A. P. P. (Jurnal Peternakan Tropika, 2022)
This study aims to examine the effect of the addition of yeast culture in the ration as a probiotic on the production performance of crossed Landrace Pigs in the starter phase. This research was conducted in Banjar Kamasan, Dajan Peken Village, Tabanan Regency. This study consisted of four treatments, namely: P0: Crossed Landrace pigs fed rations without yeast culture as a control; P1: Crossed Landrace pigs fed ration with yeast culture at 0.1%; P2: Crossed Landrace pigs fed ration with yeast culture by 0.2%; and P3: Crossed Landrace pigs fed ration with yeast culture at 0.3%. Each treatment consisted of four replications using a Completely Randomized Design (CRD). The variables observed in this study were ration consumption, final body weight, weight gain and feed conversion ratio (FCR). The results of this study showed that the addition of yeast culture in the diet as a source of probiotics of 0.1%, 0.2%, 0.3% had a significant effect (P<0.05) on final body weight gain, and FCR compared to pigs. given the ration without the addition of yeast cukture, but the effect was not significant (P> 0.05) on the consumption of the ration. The conclusion of this research is that the addition of yeast culture in the cross-bred Landrace Pig ration by 0.1-0.3% can increase the final body weight, increase body weight, and can reduce the Feed Conversion Ratio (FCR). Keywords: yeast culture, probiotics, feed conversion ratio (RCR), crossbred landrace pigs